A framework for understanding game-based teaching and learning. Issue 1 (8th February 2016) - Holmes, Jeffrey B.; Gee, Elisabeth R.
Abstract : Purpose: – This paper aims to provide a framework for understanding and differentiating among different forms of game-based teaching and learning (GBTL). Design/methodology/approach: – The framework is based on an analysis of existing literature and descriptions of GBTL in varied higher education settings, combined with case examples of the author's personal experience as instructors of GBTL courses. Findings: – Four frames or categories of GBTL approaches were identified: the action frame, the structuring frame, the bridging frame and the design frame. Each frame represents a spectrum of related yet varied strategies and assumptions. Originality/value: – This framework is a first attempt at providing an analytic tool for making sense of the varied instantiations of GBTL in higher education. It can be useful as a heuristic tool for researchers as well as a generative model for designing future GBTL practices.